BRAF and RAS mutations as prognostic factors in metastatic colorectal cancer patients undergoing liver resection - Schirripa, M (Br J Cancer, 2015)
BACKGROUND: Despite major advances in the management of metastatic colorectal cancer (mCRC) with liver-only involvement, relapse rates are high and reliable prognostic markers are needed. METHODS: To assess the prognostic impact of BRAF and RAS mutations in a large series of liver-resected patients, medical records of 3024 mCRC patients were reviewed. Eligible cases undergoing potentially curative liver resection were selected. BRAF and RAS mutational status was tested on primary and/or metastases by means of pyrosequencing and mass spectrometry genotyping assay. Primary endpoint was relapse-free survival (RFS). RESULTS: In the final study population (N=309) BRAF mutant, RAS mutant and all wild-type (wt) patients were 12(4%), 160(52%) and 137(44%), respectively. Median RFS was 5.7, 11.0 and 14.4 months respectively and differed significantly (Log-rank, P=0.043). At multivariate analyses, BRAF mutant had a higher risk of relapse in comparison to all wt (multivariate hazard ratio (HR)=2.31; 95% CI, 1.09–4.87; P=0.029) and to RAS mutant (multivariate HR=2.06; 95% CI, 1.02–4.14; P=0.044). Similar results were obtained in terms of overall survival. Compared with all wt patients, RAS mutant showed a higher risk of death (HR=1.47; 95% CI, 1.05–2.07; P=0.025), but such effect was lost at multivariate analyses. CONCLUSIONS: BRAF mutation is associated with an extremely poor median RFS after liver resection and with higher probability of relapse and death. Knowledge of BRAF mutational status may optimise clinical decision making in mCRC patients potentially candidate to hepatic surgery. RAS status as useful marker in this setting might require further studies.